(untitled) (Washington, D.C., 2001)
It examines compelling issues in the field of race relations, including: race and ethnicity in criminal justice; demographic and social trends for Hispanics, Asian Americans, and Native Americans; trends in minority-owned businesses; wealth, welfare, and racial stratification; residential segregation and the meaning of "neighborhood"; disparities in educational test scores among races and ethnicities; health and development for minority children, adolescents, and adults; race and ethnicity in the labor market, including the role of minorities in America's military; immigration and the dynamics of race and ethnicity; the changing meaning of race; and changing racial attitudes. Volume 1 specifically covers demographic trends, immigration, racial attitudes, and the geography of opportunity.
Keywords: Minorities,Minorities; Social conditions,Research,Economic conditions,Research; United States,United States